Lifestyle Risk Factors and All-Cause and Cause-Specific Mortality: Assessing the Influence of Reverse Causation in a Prospective Cohort of 457,021 Us Adults - De Moraes-Ferrari, G (Springer Science and Business Media B.V., 2022)
Background: Lifestyle risk factors have been associated with increased all-cause and cause-specific mortality, but the influence of reverse causation has been underappreciated as a limitation in epidemiological studies. Methods: Prospective cohort study including 457,021 US adults from the National Health Interview Survey 1997–2013 linked to the National Death Index records through December 31, 2015. Multivariable Cox models were performed to examine the association of lifestyle risk factors with all-cause and cause-specific mortality. Participants with prevalent diseases and the first 2, 5, 10, and 15 years of follow-up were excluded to account for reverse causation. Results: During 4,441,609 person-years, we identified 60,323 total deaths. Heavy alcohol drinking (HR 1.12; 95% CI 1.08 to 1.16), smoking (HR 1.78; 95% CI 1.74 to 1.83) and lack of physical activity (HR 1.51; 95% CI 1.47 to 1.54) were associated with increased all-cause mortality. Overweight was associated with lower all-cause mortality (HR 0.88; 95% CI 0.86 to 0.90). After exclusion of participants with diseases and first 10 years of follow-up, associations changed to: heavy alcohol drinking (HR 1.31; 95% CI 1.20 to 1.43), smoking (HR 1.99; 95% CI 1.87 to 2.11), lack of physical activity (HR 1.21; 95% CI 1.15 to 1.27), and overweight (HR 1.05; 95% CI 1.00 to 1.10). Conclusions: Methods to account for reverse causation suggest different effects of reverse causation on the associations between lifestyle risk factors and mortality. Exclusion of participants with diseases at baseline, and exclusion of 5–10 years of follow-up may be necessary to mitigate reverse causation. © 2021, Springer Nature B.V.